2021
DOI: 10.1364/ome.425827
|View full text |Cite
|
Sign up to set email alerts
|

Direct generation of optical vortex arrays by rotating in an all-solid-state Yb:CALGO laser

Abstract: We report the direct generation of optical vortex arrays in a diode-pumped bulk Yb:CALGO laser. By adjusting the angles of the input mirror, output coupler and laser crystal to achieve off-axis-pumped condition, the ring-shaped LG0,±1, two to six order vortex array have been obtained. The phase singularities of optical vortex arrays were tunable from 1 to 6. When the pump power was 13.41 W, the maximum output power of LG0,±1, double-vortex array, three-vortex array and four-vortex array were 1.93 W, 1.5 W, 1.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In 2021, they realized a tunable topological charge as high as 18th with an axicon [48]. Off-axis pumping [49][50][51][52][53][54][55] is to achieve the asymmetric pumping condition, which can efficiently hinder the oscillation of low-order modes. It is realized mainly by tilting the crystal or shifting the position of the pump spot on the crystal.…”
Section: Vortex Beam Generationmentioning
confidence: 99%
“…In 2021, they realized a tunable topological charge as high as 18th with an axicon [48]. Off-axis pumping [49][50][51][52][53][54][55] is to achieve the asymmetric pumping condition, which can efficiently hinder the oscillation of low-order modes. It is realized mainly by tilting the crystal or shifting the position of the pump spot on the crystal.…”
Section: Vortex Beam Generationmentioning
confidence: 99%
“…An alternative vortex beam generator was also demonstrated with a mirror curvature dynamically controlled Z-shaped resonator in Figure 3c [85]. Researchers also found that by rotating the Yb:CALGO crystal in the cavity, vortex arrays could be produced directly as well [86]. Another interesting structured beam is the conical refraction (CR) light, i.e., a hollow cylinder light with annular intensity profile after the beam propagates conically through a laser crystal [87].…”
Section: Mode-tunable Structured Light Lasers With Yb:calgomentioning
confidence: 99%
“…[28,29] Optical vortex arrays were obtained in a Yb:CALGO laser by rotating crystal to break cavity symmetry. [30] Optical vortex arrays were directly generated in a Yb 3+ :Y 3 AL 5 O 12 (Yb:YAG) microchip laser under tilted annular beam pumping. [31] 1D optical vortex arrays with tunable singularities and high peak power have been generated in a passively Q-switched microchip laser pumped with a decentered annular beam.…”
Section: Introductionmentioning
confidence: 99%